“I shall be on the lips of all Greece (62. 6)”: Troy in book 9 of Greek Anthology (Circe de clásicos y modernos, 2018)
In the declamatory and descriptive poems which GA 9 gathers, a source of inspiration is the destruction of Troy, sung by Homer, and the enclave of Minor Asia is linked with Mycenae or Rome and with critical situations like enmity of the gods, the collapse of the city and their protagonists’ ups and downs. This exploratory-analytical research aims to verify in thirteen selected texts which reasons, consequences and episodes related to the above mentioned warlike conflict are central and coincident –among other causes, because of the interaction between repertoires– and what details each poet contributes with, in agreement with the permanence of such components in Greek collective imaginary.
Keywords: Greek Anthology; epigrammatic genre; Troy; collective imaginary